Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/sj.bjp.0702075
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for endothelin ETB receptors in fever induced by LPS (E. coli) in rats

Abstract: 1 The in¯uence of endothelin receptor antagonists on febrile responses to E. coli lipopolysaccharide (LPS), interleukin-1b (IL-1b), tumour necrosis factor-a (TNF-a) and endothelin-1 (ET-1) was assessed in conscious rats. 2 Intravenous (i.v.) LPS (5.0 mg kg 71 ) markedly increased rectal temperature to a peak of 1.308C over baseline at 2. 4 Central injection of endothelin-1 (0.1 to 3 fmol, i.c.v.) caused slowly-developing and long-lasting increases in rectal temperature (starting 2 h after administration and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 55 publications
(60 reference statements)
5
44
0
2
Order By: Relevance
“…In our laboratory, it was shown that ␣-helical CRF 9 -41 antagonist (dual CRF 1 / CRF 2 receptor antagonist) blocks the fever induced by MIP-1␣ (Soares DM and Souza GE, unpublished observations), suggesting that the fever induced by this chemokine depends on CRF, which possibly recruits the opioidergic system. Fabricio et al (25) demonstrated that intracerebroventricular administration of ET-1 or intravenous administration of LPS induced an ET B , but not ET A , receptor-dependent increase in T b . We demonstrated in this study that the fever induced by ET-1 was completely abolished by this antagonist, suggesting that ET-1 subsequently would induce endogenous opioid release.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, it was shown that ␣-helical CRF 9 -41 antagonist (dual CRF 1 / CRF 2 receptor antagonist) blocks the fever induced by MIP-1␣ (Soares DM and Souza GE, unpublished observations), suggesting that the fever induced by this chemokine depends on CRF, which possibly recruits the opioidergic system. Fabricio et al (25) demonstrated that intracerebroventricular administration of ET-1 or intravenous administration of LPS induced an ET B , but not ET A , receptor-dependent increase in T b . We demonstrated in this study that the fever induced by ET-1 was completely abolished by this antagonist, suggesting that ET-1 subsequently would induce endogenous opioid release.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ET-1 also participates in the febrile response induced by the i.p. injected zymosan (present study) and LPS [16] but not polyinosinic:polycytidylic acid [28], suggesting that ET-1 participates in the febrile response induced by bacteria and fungus but not viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Fabrício et al [16] showed that endothelin-1 (ET-1) induced fever when it was injected directly in the brain, and that the ET B receptor antagonist BQ788 reduced LPS-induced fever. These results and those of the following studies [17,18] confirmed that ET-1 is a central mediator of fever.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that while the reduced fever response on fasting is partly attributable to an attenuated central PGE 2 production, the leptin-mediated recovery of fever is not. We also examined the levels of other inflammatory variables that were reported to contribute to the fever response independent of PGE 2 synthesis (3,7,12,37,38). Neither the levels of CSF 15-D-PGJ 2 , MIP-1␤, endothelin-1, NOS-1, NOS-2, nor NOS-3 mRNA was associated with the degree of sustained fever (Table 3).…”
Section: Febrigenic Inflammatory Responses In the Periphery And The Bmentioning
confidence: 99%